Large-Scale Forest Modeling: Deducing Stand Density from Inventory Data. (17th October 2011) - Franklin, Oskar; Moltchanova, Elena; Kraxner, Florian; Seidl, Rupert; Böttcher, Hannes; Rokityiansky, Dimitry; Obersteiner, Michael
Abstract : While effects of thinning and natural disturbances on stand density play a central role for forest growth, their representation in large-scale studies is restricted by both model and data availability. Here a forest growth model was combined with a newly developed generic thinning model to estimate stand density and site productivity based on widely available inventory data (tree species, age class, volume, and increment). The combined model successfully coupled biomass, increment, and stand closure (=stand density/self-thinning limited stand density), as indicated by cross-validation against European-wide inventory data. The improvement in model performance attained by including variable stand closure among age cohorts compared to a fixed closure suggests that stand closure is an important parameter for accurate forest growth modeling also at large scales.